Genome-wide identification of Hsp70 genes in channel catfish and their regulated expression after bacterial infection. (February 2016) - Song, Lin; Li, Chao; Xie, Yangjie; Liu, Shikai; Zhang, Jiaren; Yao, Jun; Jiang, Chen; Li, Yun; Liu, Zhanjiang
Abstract: Heat shock proteins 70/110 (Hsp70/110) are a family of conserved ubiquitously expressed heat shock proteins which are produced by cells in response to exposure to stressful conditions. Besides the chaperone and housekeeping functions, they are also known to be involved in immune response during infection. In this study, we identified 16 Hsp70/110 geness in channel catfish ( Ictalurus punctatus ) through in silico analysis using RNA-Seq and genome databases. Among them 12 members of Hsp70 (Hspa) family and 4 members of Hsp110 (Hsph) family were identified. Phylogenetic and syntenic analyses provided strong evidence in supporting the orthologies of these HSPs. In addition, we also determined the expression patterns of Hsp70/110 genes after Flavobacterium columnare and Edwardsiella ictaluri infections by meta-analyses, for the first time in channel catfish. Ten out of sixteen genes were significantly up/down-regulated after bacterial challenges. Specifically, nine genes were found significantly expressed in gill after F. columnare infection. Two genes were found significantly expressed in intestine after E. ictaluri infection. Pathogen-specific pattern and tissue-specific pattern were found in the two infections. The significantly regulated expressions of catfish Hsp70 genes after bacterial infections suggested their involvement in immune response in catfish. Highlights: A full set of 16 Hsp70/110s were characterized from the channel catfish genome. Nine genes were found significantly expressed in gill after F. columnare infection. Two genes were found significant expressed in intestine after E. ictaluri infection. Pathogen-specific pattern, tissue-specific pattern and time pattern are found in the two infections. More Hsp70/110 genes and higher expression fold change are found in gill after F. columnare infection than that in intestine after E. ictaluri infection. However higher RPKM of catfish Hsp70/110s was found in intestine before and after E. ictaluri infection than that in gill before and after F. columnare infection. This indicates that the Hsp70/110s are more inducible in gill after F. columnare infection.